Assembly of food proteins for nano- encapsulation and delivery of nutraceuticals (a mini-review) - Tang, Chuan-He (Food hydrocolloids, 2021)
Incorporation of hydrophobic and poorly soluble nutraceuticals into food formulations is among the great challenges in food science and pharmaceutical fields. One effective strategy to meet this challenge is to develop a kind of food-compatible nanovehicles for improving water solubility, stability, bioavailability and bioactivities of these nutraceuticals. Many food protein-based nano-architectures, e.g., nanoparticles, nano-complexes, nanogels, nano-micelles, nanofibers or nanotubes, have been demonstrated to perform as outstanding nanovehicles in this regard. They are not only nutritional/digestible, safe, and easy to prepare and handle, but also have high encapsulation performance and nutraceutical loading capacity. In some cases, the encapsulation in these nanovehicles can impart an intestine-targeted and controlled delivery function to encapsulated nutraceuticals. In this paper, the assembly of milk and soy proteins into a variety of nano-architectures, as potential nanovehicles for hydrophobic nutraceuticals is critically reviewed. The strategies to trigger the assembly, or disassembly/reassembly of naturally occurring nano-architectures (e.g., native soy oligomeric globulins and casein micelles), denatured and aggregated proteins (e.g., soy protein isolate and whey protein isolate), and monomeric globular proteins (e.g., β-lactoglobulin) are highlighted. The general principles of protein self-assembly are also discussed. Due to the fast increasing interests for the incorporation of hydrophobic nutraceuticals in many novel food formulations, this review is of relevance for providing a state-of-art knowledge about the strategies and approaches to develop food protein-based nano-architectures as effective nanovehicles for nutraceuticals. [Display omitted] •Food proteins exhibit a great potential in nanoencapsulation of nutraceuticals.•General principles of protein self-assembly are presented.•Soy and milk proteins can form versatile nano-architectures via different strategies.•Strategies to trigger the assembly of soy and milk proteins into nano-architectures are highlighted.•Natural architectures (casein micelles and soy globulins) can perform as nanovehicles for nutraceuticals.